Lettres persanes - Montesquieu, Charles de Secondat 1689-1755 (Amsterdam s.n., 1786)
'Persian Letters' is a literary work recounting the experiences of two fictional Persian noblemen, Usbek and Rica, who spend several years in France under Louis XIV and the Regency. Lettres persanes was an immediate and durable sensation and was often imitated, but it has been diversely read over time. Until the middle of the twentieth century, it was the "spirit" of the Regency which was largely admired, as well as the caricature in the classical tradition of La Bruyère, Pascal and Fontenelle. No one thought to attach it to the novelistic genre. The Persian side of the story tended to be considered as a fanciful decor, the true interest of the work lying in its factitious "oriental" impressions of French society, along with political and religious satire and critique. In the 1950s began a new era of studies based on better texts and renewed research.
Includes an index
Originally published in 1721
Marbled end papers and edges, leather bound, embossed gilt spine
Augmentée de douze lettres qui ne se trouvent point dans les précédentes, et d'une table des Matieres
Keywords: 18th Century (1701-1800); Philosophy; Novel; Correspondence; Satire; Enlightenment; France; Persian Empire